Policies, textbooks and the curriculum as constraints to integrating literature into language education - Calafato, Raees (Sodobna pedagogika, 2019)
Employing a qualitative design, this exploratory study examined the challenges and constraints encountered by foreign language teachers in Russia when using literature in their lessons in primary, secondary and tertiary education. Consisting of interviews with nine Russian English as a Foreign Language (EFL) teachers, the study's findings indicate that education policies, a strong focus on standardised testing, poor quality textbooks and a lack of institutional support are not only hindering the wider adoption of literary texts as a language resource but are also likely hampering language learning for students. The study presents policymakers as well as school and university administrators with insights into the structural issues that might be preventing foreign language teachers from more effectively integrating literature into their lessons and offers recommendations that could help them to formulate policies and strategies that address these issues.
Keywords: angleščina; izobraževalna politika; izobraževanje učiteljev; kurikulum; literarna besedila; pouk tujega jezika; učbeniki; učne metode